PENGARUH RUGI-RUGI SALURAN PADA JARINGAN TRANSMISI TEGANGAN MENENGAH PENYULANG E2 GARDU INDUK EMBALUT TENGGARONG - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
A good electric power system must have a voltage value that does not exceed the tolerance limit and small power losses. The tolerable limit for a voltage value (+ 5%; - 10%) of its nominal value. A constant voltage value will optimize the performance of the electrical equipment used by the consumer. While the small power losses will keep the power supply in accordance with the needs of consumers, and can reduce financial losses that occur during the transmission and distribution process. In this thesis will be a study to improve the quality of stress on the distribution network by reconfiguring the network. The process of repair is done on medium voltage network by opening or closing Fuse Cut Out, Load Break Switch, Disconnecting Switch, adding substation insertion, and change the position of Process Tap Changer to provide the most optimum repair value. Improved voltage on this thesis is simulated using ETAP 12.6.0 software. From the simulation results will be obtained the most optimal voltage improvement is in the case study 1 on the most bus end of the Bus GRA 706 with a voltage of 16.12 kV, case study 2 voltage rose to 19.66 kV and case study 3 voltage to 19,661 kV.